STUDI KASUS GAMBARAN SKALA NYERI ANAK PRASEKOLAH DENGAN MENGGUNAKAN WONG-BAKER FACES PAIN RATING SCALE (WBFPRS) SAAT PROSEDUR PENGAMBILAN DARAH VENA - Faizah Faizah; Ganis Indriati; Arneliwati Arneliwati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2019)
Venipuncture can cause pain, especially in preschool children. Untreated pain have a devastating effect on a child's physiology and psychology. The purpose of this research is to describe the scale of pain using the Wong-Baker FACES Pain Rating Scale (WBFPRS) during the venipuncture procedure in preschool children. This research is an observational descriptive design with a case study approach. The sample is 14 respondents taken based on inclusion criteria using accidental sampling technique. The measurement instrument used a questionnaire for demographic data and observation sheet of WBFPRS. The analysis used is simple descriptive to describe the research distribution and percentage of respondent’s characteristics and variables. The results found that most respondents aged 3 years were 6 people (42.9%), most respondents were male 8 people (57.1%), and all (100%) respondents experienced with previous pain experiences. This research found that most respondents experienced very severe pain were 6 people (42.9%). This study recommends that the installation of health services related to children can implement atraumatic care so that respondent’s pain scale were reduced. Keyword: pain, preschool, venipuncture